A metaficção historiográfica no romance A filha do escritor - Vezzaro, Bernardo Antonio (2012)
This work investigates the presence of historiographic metafiction in the novel A filha do escritor, from the author Gustavo Bernardo. For this purpose, the following elements were analyzed in the narrative: the reference to reality and its recovery, the eccentric characters and the intertextuality with the works O alienista and Ressureição, from Machado de Assis. The research, constituted by a bibliographical work, had as theoretical premises the studies of Linda Hutcheon creator of the term historiographic metafiction presented in the work titled Poética do pós-modernismo: história, teoria, ficção, published in 1987, besides the studies around metafiction developed by the author of the novel himself, Gustavo Bernardo, reunited in the work O livro da metaficção, released in 2010